2012
DOI: 10.1186/bcr3324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hormone receptor status on patterns of recurrence and clinical outcomes among patients with human epidermal growth factor-2-positive breast cancer in the National Comprehensive Cancer Network: a prospective cohort study

Abstract: IntroductionIn gene expression experiments, hormone receptor (HR)-positive/human epidermal growth factor-2 (HER2)-positive tumors generally cluster within the luminal B subset; whereas HR-negative/HER2-positive tumors reside in the HER2-enriched subset. We investigated whether the clinical behavior of HER2-positive tumors differs by HR status.MethodsWe evaluated 3,394 patients who presented to National Comprehensive Cancer Network (NCCN) centers with stage I to III HER2-positive breast cancer between 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
80
5
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 48 publications
15
80
5
5
Order By: Relevance
“…HR positivity was associated with a favorable DFS and OS. The discrepancy with our data could be attributed to the unbalanced groups in the study by Vaz-Luis et al (2012). Similar to our collective, HR− tumors were more likely to present unfavorable prognostic factors such as a higher histological grade.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…HR positivity was associated with a favorable DFS and OS. The discrepancy with our data could be attributed to the unbalanced groups in the study by Vaz-Luis et al (2012). Similar to our collective, HR− tumors were more likely to present unfavorable prognostic factors such as a higher histological grade.…”
Section: Discussioncontrasting
confidence: 97%
“…This is consistent with several prior studies describing different rates of recurrence and hazard of death depending on HR status (Dignam et al 2009, Early Breast Cancer Trialists' Collaborative Group et al 2011, Vaz-Luis et al 2012, Strasser-Weippl et al 2015 suggesting that HR− and HR+ HER2+ breast cancer represent two different entities (Burstein 2005). In this regard, our observations highlight the fact that HR status remains an important prognostic factor regardless of HER2 status and trastuzumab treatment.…”
Section: :5supporting
confidence: 92%
See 2 more Smart Citations
“…Also ER positivity was greater in patients 50 years of age or older (Goyanes et al, 2010). In contrast patients with Her 2 neu positivity are younger, present with higher T stage, nodal involvement and higher grade (Vaz-Luis et al, 2012). Studies have also shown that patients who are ER, PR positive and Her 2 neu negative have decreased incidence of both local and distant recurrence as compared to those who are ER, PR negative and Her 2 neu positive (Shim et al, 2014).…”
Section: 1019 Impact Of Tumour and Factors On Survival Of Breast Canmentioning
confidence: 99%